Using combinatorial testing to build navigation graphs for dynamic web applications. (2nd February 2016) - Wang, Wenhua; Sampath, Sreedevi; Lei, Yu; Kacker, Raghu; Kuhn, Richard; Lawrence, James
Summary: Modelling a software system is often a challenging prerequisite to automatic test case generation. Modelling the navigation structure of a dynamic web application is particularly challenging because of the presence of a large number of pages that are created dynamically and the difficulty of reaching a dynamic page unless a set of appropriate input values are provided for the parameters. To address the first challenge, some form of abstraction is required to enable scalable modelling. For the second challenge, techniques are required to select appropriate input values for parameters and systematically combine them to reach new pages. This paper presents a combinatorial approach in building a navigation graph for dynamic web applications. The navigation graph can then be used to automatically generate test sequences for testing web applications. The novelty of our approach is twofold. First, we use an abstraction scheme to control the page explosion problem, where pages that are likely to have the same navigation behaviour are grouped together and are represented as a single node in the navigation graph. Second, assuming that values of individual parameters are supplied manually or generated from other techniques, we combine parameter values such that well‐defined combinatorial coverage of input parameter values is achieved. Using combinatorial coverage can significantly reduce the number of requests that have to be submitted while still achieving effective coverage of the navigation structure. We implement our combinatorial approach in a tool, Tansuo, and apply the tool on seven open‐source web applications. We evaluate the effectiveness of Tansuo 's exploration process guided by t ‐way coverage, for t = 1, 2, 3, with respect to code coverage, and find that the navigation structure exploration by Tansuo, in general, results in high code coverage (more than 80% statement coverage for most of our subject applications when dead code is removed). We compare Tansuo 's effectiveness with two other navigation graph tools and find that Tansuo  is more effective. Our empirical results indicate that using pairwise coverage in Tansuo  results in the efficient generation of navigation graphs and effective exploration of dynamic web applications. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We present an approach to model the navigation structure of dynamic web applications by applying combinatorial strategies for systematic coverage of the navigation structure. We implement our approach in a tool, Tansuo, and experimentally evaluate its effectiveness on seven web applications with exploration guided by t ‐way coverage, for t = 1, 2, 3. We find that 2‐way coverage is most effective and can cover more than 80% of the underlying code.